The EIB Circular Economy Guide Supporting the circular transition - Investment Bank, European (European Investment Bank, 2020)
The EIB Circular Economy Guide aims to promote a common understanding of circular economy, and raise awareness about and promote circular solutions. The Guide provides information about EIB's lending and advisory activities in this field, and communicates our vision of how the EIB can further support the transition to a circular economy. The Guide is a living document that will be updated in response to our evolving understanding of circular economy needs, opportunities and risks, and growing experience with the appraisal and financing of circular economy projects.
Description based on print version record.
KU Open Services
Keywords: Business & Economics / Finance; Economics; Electronic books